Tractography-based DBS lead repositioning improves outcome in refractory OCD and depression - Basich-Pease, Genevieve; Slepneva, Natalya; Frank, Adam C.; Norbu, Tenzin; Morrison, Melanie A.; Sugrue, Leo P.; Larson, Paul S.; Starr, Philip A.; Lee, A. Moses (Frontiers in Human Neuroscience, 2024)
Deep brain stimulation (DBS) of the anterior limb of the internal capsule (ALIC) has been used to treat refractory obsessive-compulsive disorder (OCD) and depression, but outcomes are variable, with some patients not responding to this form of invasive neuromodulation. A lack of benefit in some patients may be due to suboptimal positioning of DBS leads. Recently, studies have suggested that specific white matter tracts within the ALIC are associated with improved outcomes. Here, we present the case of a patient who initially had a modest improvement in OCD and depressive symptoms after receiving DBS within the ALIC. Subsequently, he underwent a unilateral DBS lead repositioning informed by tractography targeting the ventrolateral and medial prefrontal cortex's connection with the mediodorsal thalamus. In this patient, we also conducted post-implant and post-repositioning diffusion imaging and found that we could successfully perform tractography even with DBS leads in place. Following lead repositioning into tracts predictive of benefit, the patient reached responder criteria for his OCD, and his depression remitted. This case illustrates that tractography can potentially be used in the evaluation and planning of lead repositioning to achieve therapeutic outcomes.